(untitled) (Docentes 2.0 Journal, 2023)
Assessment in education has been an important part of teachers’ work, making it difficult to introduce change in this area. The study’s objective was to analyze the current state of reflective feedback in the learning of mathematics to guarantee an improvement in the teaching and learning processes. The research was carried out using the systematic method, hermeneutic paradigm, qualitative approach with thematic narrative design, and informative documentary type of the electronic articles contained in various scientific journals indexed to the electronic databases Scopus, Web of Science, Redalyc, and Scielo, 14 scientific journals—productions, published in Spanish, English, and Portuguese. In the content analysis, it was possible to observe some trends in the methodological approach, type of journal, and number of annual publications in the quantitative synthesis. On the other hand, the qualitative synthesis indicates that for reflective feedback in mathematics to be effective, the teacher, in addition to using feedback tools such as Wilson’s ladder, needs to have a specific area of learning, skills, and evidence of learning. In conclusion, the teacher needs to add pedagogical knowledge to the disciplinary knowledge of his subject.